(untitled) (Global Journal of Science Frontier Research, 2016)
This study was conducted from November 2014 -May 2015 to determine the antimicrobial resistance pattern of Staphylococcus species in poultry in Central and Southern Ethiopia. 205 staphylococcal species isolated from poultry were evaluated using disk diffusion method for their antimicrobial susceptibility to 10 different antimicrobial drugs. Staphylococcus were found to be highly susceptible to Ciprofloxacin (85.4%) followed by Sulfamethoxazole-Trimethoprim (68.8%). However these isolates were highly resistant to Penicillin G (94.1%) and Tetracycline (79%) followed by Amoxicillin (60.5%). From all Staphylococci isolates tested for drug susceptibility pattern, only 1 isolate (S. aureus) was susceptible to all tested drugs and 99.51% of isolates were resistant to at least one of the antibiotics tested. Coagulase negative Staphylococci were highly resistant to all tested drugs except Ciprofloxacin (0%) and S. aureus were highly resistant to Penicillin G (92.2%) and Tetracycline (74.5%). Staphylococcus species isolated in poultry in Central and Southern Ethiopia were all multidrug resistant.